2020
DOI: 10.26719/emhj.20.045
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of infants’ feeding and weaning in Suez Governorate, Egypt: an exploratory study

Abstract: Background: Breastfeeding and proper weaning contribute to achievement of the Sustainable Development Goals. In Egypt, by age 4-5 months, only 13% of infants are exclusively breastfed. A survey conducted in Egyptian hospitals concluded that many of the 10 steps to support successful breastfeeding were not executed correctly and other steps were not executed at all. Aims: To explore the patterns of feeding and weaning among infants in Egypt, and identify their determinants, to improve practice and promote child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This result was confirmed by Firdausya & Hardini [17] , who stated that near two-third of the studied mothers offered exclusive breastfeeding to their infants. This result contradicted with findings of Kamel, Sabry, Ismail, & Nasr [18] studied ''Pattern of infants' feeding and weaning in Suez Governorate, Egypt: an exploratory study'' and reported that most infants were ever breastfed. Exclusive breastfeeding was not widely practiced.…”
Section: Discussioncontrasting
confidence: 67%
“…This result was confirmed by Firdausya & Hardini [17] , who stated that near two-third of the studied mothers offered exclusive breastfeeding to their infants. This result contradicted with findings of Kamel, Sabry, Ismail, & Nasr [18] studied ''Pattern of infants' feeding and weaning in Suez Governorate, Egypt: an exploratory study'' and reported that most infants were ever breastfed. Exclusive breastfeeding was not widely practiced.…”
Section: Discussioncontrasting
confidence: 67%
“…The weighted average prevalence of ever breastfed in the EMR was estimated at 84.3% ( Table 1 ). Ever breastfed prevalence was higher than 95% in United Arab Emirates (95.3%) [ 16 , 17 ], Libya (95.6%) [ 18 ], Qatar (96%) [ 19 , 20 , 21 ], Sudan (96%) [ 22 ], Pakistan (96.8%) [ 23 , 24 , 25 ], Egypt (97.7%) [ 26 , 27 , 28 ], with the highest rate reached in Iran (98.6%). The lowest rates of ever breastfed were reported from Oman (47%) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lowest rates of ever breastfed were reported from Oman (47%) [ 29 ]. Over time, an increasing trend in ever breastfed prevalence was noticed in Lebanon [ 4 , 30 , 31 ], Egypt [ 26 , 27 , 28 ] and Kuwait [ 32 , 33 , 34 ] ( Table S1 ). As for Afghanistan, Bahrain, Djibouti, Palestine, Somalia and Syrian Arab Republic, no data was reported concerning ever breastfed prevalence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable minority among our participating women fed their infants under four times daily and, hence, scored a significantly lower average knowledge score. Underfeeding remains a substantial problem when weaning infants, particularly in rural communities [ 28 ]. On a positive note, recent estimates for frequency of complimentary feeding were regarded as satisfactory in rural India, exceeding 75% [ 29 ].…”
Section: Discussion Of Key Findingsmentioning
confidence: 99%